The Effect of the Cognitive Research Trust Program for Development of Thinking Skills on the Achievement of the Jordanian English Language Learners - Hmeadat, Samer Radwan Ahmed (Arab Journal for Sciences and Research Publishing, 2016)
Aim: To investigate the effect of the CoRT(Cognitive Research Trust) program for the development of thinking skills on the achievement of the Jordanian English language learners. The length of the program did not exceed more than three months and a half, starting from the warming-up period in the first semester to the achievement test. Methods: The study sample consisted of (86) students from the seventh grade in Al Nahda Islamic Modern Private Schools, The First Directorate of Education in Zarqa District. The subjects were divided into four groups. Two experimental groups consisted of (34) male students who were taught two units in the curriculum (Aim High1) through the CoRT program. The other two control groups consisted of (34) male students who were taught the same content through the conventional strategy. Analysis of ANOVA was performed to test the statistical significance of the differences between the experimental group who was taught through the CoRT and the control group who was taught through the conventional method. Result: It revealed that there was a statistical significant difference at the level (α =0.05) in the mean scores between the experimental group and the control group in favor of the experimental group. Interestingly, the current study adopted the experimental design. Conclusion: There were statistically significant differences between the mean scores of the subjects of the experimental groups who studied through the CoRT as a new instructional model and the control group who studied through the conventional method in favor of the experimental groups.
Keywords: CoRT program strategies; conventional method; seventh grade students; training program cognitive research trust